How COVID-19 pandemic affected nutrition behaviors - Pittara Pansawira (World Nutrition Journal, 2023)
Coronavirus disease (COVID-19) had started as a global pandemic and public health emergency back in year 2020. Starting in year 2023, which was a little more than three years afterwards, World Health Organization (WHO) removed COVID-19’s public health emergency status.1 During the past three years, the pandemic, quarantine, and lockdown policy had changed many aspects in life, sosio-economic and public health alike. This included nutrition behaviors which significantly affected the global population’s nutritional status. A study to adults and elderly living independently in Amsterdams revealed an increase of nutritional behavior presdisposing to overnutrition, such as more snacking and decreased physical activity to those who had not been in quarantine. Whereas those who were in quarantine, behavior changes related to undernutrition, such as eating less, skipping meals, and drinking more alcoholic beverages, were more seen in the study results.2 An online survey study to lockdown countries e.g Europe, North-Africa, Western Asia, and United States showed a decrease in both frequency and the duration of physical activity, included an increase of time spent in sedentary behavior. The study also revealed a significant increase in consuming unhealthy food, eating out of control, snacking between meals, alcohol binge drinking, and number of main meals per day.3An online study to students in Indonesia showed changes in eating patterns consisted of increased meal portions and snacks. The sedentary behavior was also excalated.4 What factors contributed to these changes? As we all aware, confinement influence our daily activities and mental health. Those who usually commute to the office had to work from home thus limiting physical activities. We also saw the increased numbers of anxiety, depression, and boredom which may led to more snackings or skipping meals.We had learned that the restriction to stay at home had influenced dietary and physical activity. These changes may or may not expected, however, they surely altered global nutritional status. The numbers of overweight and obesity are more prevalent post-pandemic thus may lead to the increase of non-communicable diseases.We certainly hope that there will be no more pandemic which warrants lockdown in the future, however the future itself is not a certainty. In the present, we will have to tackle many nutritional-related problems in any population. Within the course of time, if a similar pandemic should occur, we might have to compile a public health, nutrition, mental health, and physical activity policy to minimize the problems.